Optimal production/inventor control for a two-machine make-to-stock system - Qian, Yi (2008)
We consider a two-station make-to-stock system with unreliable machines. Items are stocked in the finished goods inventory after production and serve an exogenous demand. Unfulfilled demand is backordered. The objective is to operate the system such that it meets demand without over-producing, under-producing or carrying excessive work-in-process inventory. The optimal control policy can be numerically obtained from the solution the dynamic programming equations. Based on the structure characteristics of the optimal control, an approximate sub-optimal control policy, two-boundary control, was developed that divided the state space into distinct regions and used only simple hedging-point polices in each region. Analytical methods of determining the two-boundary control parameters were presented. Performance of the two-boundary control was evaluated in simulation. Results showed that compared to that from the best CONWIP and best base stock control policies, two-boundary was able to achieve a lower average cost under both a constant demand and an exponential demand rate.